Effects of Amiodarone and Dronedarone on Voltage‐Dependent Sodium Current in Human Cardiomyocytes - Nathalie Lalevée; Stéphanie Barrère‐Lemaire; Patrick Gautier; Joël Nargeot; Sylvain Richard (2003)
Introduction: Amiodarone (AM) is a highly effective antiarrhythmic agent used in the management of both atrial and ventricular arrhythmias. Its noniodinated analogue dronedarone (SR) may have fewer side effects than AM. In this study, we compared the effects of AM and SR on the sodium current I Na in human atrial myocytes. Methods and Results: I Na was studied with the whole‐cell, patch clamp technique. Both AM and SR induced a dose‐dependent inhibition of I Na recorded at −40 mV from a holding potential of −100 mV. AM inhibited I Na by 41%± 11% (n = 4) at 3 μM, and by 80%± 7% (n = 5) at 30 μM. SR produced more potent block, inhibiting I Na significantly at only 0.3 μM (23%± 10%, n = 4) and completely (97%± 4%, n = 4) at 3 μM. Both AM and SR had only moderate effects on voltage‐dependent properties of I Na (current‐voltage relationship, availability for activation) and had no effect on the current decay kinetics. Conclusion: Both AM and SR inhibit I Na significantly in single human atrial cells, showing that the two drugs have Class I antiarrhythmic properties. The acute effects of SR are more potent than those of AM. The study supports the idea that the iodinated form of the molecule has no part in the acute effect of AM on Na + channels. (J Cardiovasc Electrophysiol, Vol. 14, pp. 885‐890, August 2003)